Synthesis of an Endogenous Steroidal Na Pump Inhibitor Marinobufagenin, Implicated in Human Cardiovascular Diseases, Is Initiated by CYP27A1 via Bile Acid Pathway. (October 2015) - Fedorova, Olga V.; Zernetkina, Valentina I.; Shilova, Victoria Y.; Grigorova, Yulia N.; Juhasz, Ondrej; Wei, Wen; Marshall, Courtney A.; Lakatta, Edward G.; Bagrov, Alexei Y.
Abstract : Background—: The bioactive steroid, marinobufagenin, is an endogenous Na/K-ATPase bufadienolide inhibitor that is synthesized by adrenocortical and placental cells. Marinobufagenin binding to Na/K-ATPase initiates profibrotic cell signaling, and heightened marinobufagenin levels are implicated in the pathogenesis of hypertension, preeclampsia, and chronic kidney disease. Steroids are derived from cholesterol through the traditional steroidogenesis pathway initiated by enzyme CYP11A1, and via the acidic bile acid pathway, which is controlled by enzyme CYP27A1. The mechanism of marinobufagenin biosynthesis in mammals, however, remains unknown. Methods and Results—: Here, we show that post-transcriptional silencing of the CYP27A1 gene in human trophoblast and rat adrenocortical cells reduced the expression of CYP27A1 mRNA by 70%, reduced total bile acids 2-fold, and marinobufagenin levels by 67% when compared with nontreated cells or cells transfected with nontargeting siRNA. In contrast, silencing of the CYP11A1 gene did not affect marinobufagenin production in either cell culture, but suppressed production of progesterone 2-fold in human trophoblast cells and of corticosterone by 90% in rat adrenocortical cells when compared with cells transfected with nontargeting siRNA. In vivo, in a high-salt administration experiment, male and female Dahl salt-sensitive rats became hypertensive after 4 weeks on a high-NaCl diet, their plasma marinobufagenin levels doubled, and adrenocortical CYP27A1 mRNA and protein increased 1.6-fold and 2.0-fold. Conclusions—: Therefore, the endogenous steroidal Na/K-ATPase inhibitor, marinobufagenin, is synthesized in mammalian placenta and adrenal cortex from cholesterol through the novel acidic bile acid pathway. These findings will help to understand the role of marinobufagenin in highly prevalent human cardiovascular diseases.